What’s poetics got to do with prophets for Farabi - Nadia Maftouni; Mahmoud Nuri (Pensamiento. Revista de Investigación e Información Filosófica, 2025)
Farabi’s utopia (al-madīnat al-fāḍila), literally meaning «the excellent state», consists of five levels. On the first level stands the philosopher (fīlsūf) or the prophet (nabī). The second level includes poets (shuʿarā), music composers (mulaḥḥinūn), writers (kuttāb) and the likes of them. Farabi strongly believes in the power of imagination (khīyāl) and that most people are under the influence of their imaginative faculty (al-quwwat al-mutakhayyila). This notion has an important outcome which influences his view on religion (milla), prophet, and their relation with the public (jumhūr): Images, in his view, are the most powerful means of influencing the public. Regarding this principle, it could be concluded that there is a shared function between the poet and the prophet. In other words, Farabi’s prophet performs, in part, a poetic task.